Dampak fenomena permainan judi online terhadap kesadaran hukum remaja di Kelurahan Pematang Kandis - Rizal, Musthofa; Anderson, Irzal; melisa, Melisa (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Online gambling games among teenagers are a disturbing phenomenon. Actions that are detrimental to the teenager or other people. This research was conducted in Pematang Kandis Bangko Village. This research is qualitative research using descriptive methods. The informants in this research are 8 teenagers who play online gambling, parents of teenagers who play online gambling and 2 residents, with data collection techniques in the form of interviews, observation and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of this research show that the majority of teenagers have a low level of legal awareness regarding the legal consequences of their participation in online gambling games, this cannot be separated from the factors that cause them to commit crimes in online gambling games, these factors are situational, social factors. and economics, perceived probability of winning and family factors. The impact of this lack of legal awareness can be seen in the behavior of teenagers who tend to ignore the laws related to online gambling even though they are aware of these laws. They may engage in gambling activities without considering the legal implications.